2021
DOI: 10.1186/s12879-021-06021-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV voluntary counseling and testing uptake and associated factors among Ethiopian youths: evidence from the 2016 EDHS using multilevel modeling

Abstract: Background Existing evidence showed that Human Immunodeficiency Virus counselling and testing uptake among Ethiopian youths is low, and factors contributing to it are not well studied. Therefore, this study aims to assess the status of uptake and identify its determinants using the 2016 Ethiopia Demographic and Health Survey data. Method Data of 10,903 Ethiopian youths were extracted from the 2016 Ethiopian Demographic and Health Survey. The associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…e funding of this study revealed that male participants were less likely to practice voluntary counseling and testing compared to female participants. is study is in line with the study conducted in the Addis Ababa university [32], Ambo University [33], in Ethiopia [34], in sub-Saharan Africa [35], in South Africa [36], in Lesotho [37], in Arusha City, Tanzania [38], and it contradicts with the study done in the West Gojjam Merawi Preparatory school [1]. It might be the awareness gap between male and female students in the high school level and also the increment of the female students confidence in the higher institution compared to the lower class.…”
Section: Discussionsupporting
confidence: 88%
“…e funding of this study revealed that male participants were less likely to practice voluntary counseling and testing compared to female participants. is study is in line with the study conducted in the Addis Ababa university [32], Ambo University [33], in Ethiopia [34], in sub-Saharan Africa [35], in South Africa [36], in Lesotho [37], in Arusha City, Tanzania [38], and it contradicts with the study done in the West Gojjam Merawi Preparatory school [1]. It might be the awareness gap between male and female students in the high school level and also the increment of the female students confidence in the higher institution compared to the lower class.…”
Section: Discussionsupporting
confidence: 88%
“…The finding that in all four countries, ever-married women were more likely to get tested for HIV is consistent with previous studies. 6,7 Ever-married women have more chances of being tested for HIV through services aimed at prevention of mother-to-child transmission (PMTCT) of HIV. Consistent with previous studies, [6][7][8] we found that HIV testing uptake of women increased as their education level increased.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found that certain socioeconomic and demographic characteristicsage, 5,6 marital status, [6][7][8] educational levels, [6][7][8] occupation, 7 wealth [5][6][7][8] and place of residence 5,8 are significantly associated with HIV testing uptake. Moreover, research has demonstrated that comprehensive knowledge of HIV is associated with higher HIV testing uptake, 5,7,9 while stigma and discrimination of HIV are associated with lower HIV testing uptake. 5 Additionally, Thapa et al 10 found that women with positive attitudes about safer sex negotiation had higher odds of being tested for HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia has gained ground in lessening the quantity of HIV/AIDS cases in the nation, yet the changes observed are defcient in contrast with the ideal objectives of the reaction to the pestilence [13,14]. Given the size of the populace and the greatness of the harm incurred, it will require a long while to see critical decreases in HIV commonness and frequency with purposeful and supported endeavors, keeping in mind that there have been progresses in the accessibility, openness, and use of HIV/AIDS anticipation, care, backing, and treatment administrations, as well as upgrades in the scourge of the executives and expanding asset accessibility, we need more endeavors to control the plague [1,[15][16][17]. Subsequently, the motivation for this study was to investigate the role of socioeconomic, HIV/ AIDS mindfulness, and sexual conduct factors in understanding the prevalence and risk factors for HIV disease among Ethiopian sexually active women.…”
Section: Introductionmentioning
confidence: 99%